The Non-Coding RNA Journal Club: Highlights on Recent Papers—10 - Jairo A. Pinzon Cortes; Assam El-Osta; Giulia Fontemaggi; Nicholas Delihas; Katsuki Miyazaki; Ajay Goel; Mira Brazane; Clément Carré; Paola Dama; Salih Bayraktar; Leandro Castellano; Francisco J. Enguita; et al. (Non-Coding RNA, 2022)
We are delighted to share with you our seventh Journal Club and highlight some of the most interesting papers published recently [...]